Drug related problems identified by clinical pharmacist at the Internal Medicine Ward in Turkey - SANCAR, MESUT (SPRINGER, 2018)
Background Drug-related problems (DRPs) interfere with patient optimal therapeutic outcomes and may be associated with higher morbidity, mortality and healthcare expenditures. Objective This study aimed to identify DRPs and their causes in a Turkish hospital. Setting Bakirkoy Dr. Sadi Konuk Teaching and Research Hospital, Internal Medicine Ward, Istanbul, Turkey. Method Cross-sectional study included a total of 100 patients. Patient demographics, medications, and history were evaluated. Data regarding recent medications were analyzed by two clinical pharmacists and an Internal Medicine physician. The DRPs were identified via V7.0 PCNE classification. Lexicomp(A (R)) was used to assess the drug-drug interactions. UpToDate(A (R)) recommendations and national guidelines were applied in the assessment of compliance with approved medication procedures. Main outcome measures Number and causes of the potential DRPs. Results At least one potential DRP was seen in 80% of the patients and 163 potential DRPs were identified (average = 1.6 DRPs/patient). The most common causes of DRPs were errors in drug selection (44.78%), dose selection (27.61%) and medication procedures (21.47%). There were significant correlations (p < 0.05) between DRPs and age (r = 0.4), number of drugs used (r = 0.32), duration of hospitalization (r = 0.25), renal impairment (r = - 0.34) and inflammation (r = 0.31). Conclusion The majority of the patients had DRPs. Patients with renal impairment, inflammation, polypharmacy or an extended hospital stay had a much higher chance of developing DRPs.
Keywords: Dose selection; Drug-related problem; Medication procedure; Renal impairment; Turkey; HOSPITAL ADMISSIONS; COST